(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article studies the artistic reflection of the national idea and the concept «Mangilik El» in works of the outstanding representative of the literary trend Zar Zaman – Murat Monkeuly (the end of XIX century – be ginning of the XX century) in the history of the Kazakh literature. It deeply investigates the traditions, glorification of the national idea and ways of involvement in the idea of the «Mangilik El». The main attention is paid to generalizing characteristics of National idea and the idea «Mangilik El». In article there has been revealed notions of love for Homeland, meaning of artistic representation of the spirit of freedom, which were eternal dream of the nation in such poems-tolgaus of the poet Murat Monkeuly as «Ush Kiyan», «Saryarka», «Karasai Kazy» where there is an artistic description of life. The article compares the process of the chanting the national idea and its identity in the poetry of Zar Zaman poets and Murat Monkeuly. There it is given the full analysis of presence and fusion of national ideas with the idea of the «Mangilik El» in Murat’s poems, which continues the tradi tion of glorification of the fighter’s spirit in works of zhyraus (narrators) as Asankaigy, Kaztugan, Dospambet and Aktamberdy.